Upaya Pencegahan Perilaku Bullying Anak Usia SD Melalui Kegiatan Sosialisasi Di SD Negeri 1 Jamblang - Ambarwati Imtiyas; Andine Rizki Kurnia; Livia Livia; Tiyara Maharani; Sati Sati; Dian Setiawati (Journal on Education, 2025)
Bullying behavior in elementary school environments often occurs due to students' lack of understanding of its negative impacts. The Student Service Program at SDN 1 Jamblang aims to prevent bullying, intolerance, and sexual violence through three phases: planning, implementation, and evaluation.The planning phase includes the creation of materials, data collection, and activity preparation. The implementation phase involves delivering materials, interactive discussions, and creating "Stop Bullying" posters. The evaluation is conducted through questionnaires to measure students' understanding.The program results showed a significant increase in students' awareness of bullying issues and positive behavioral changes. The school environment became more inclusive, the learning atmosphere more conducive, and student interactions more harmonious. However, challenges such as lack of support from relevant parties, limited resources, and resistance to changes in teaching methods need to be addressed.The success of this program provides a strong foundation for its sustainability and can serve as a model for other schools. Continued support from all stakeholders is essential to ensure the program's long-term effectiveness